Efficacy of herbicide formulations for weed control in maize in a humid tropical environment - Fontem Lum, A.; Chikoye, David (Elsevier, 2010)
Weeds are a serious constraint to maize production in the tropics. A field experiment was conducted in Cameroon, at the University of Buea Research farm in 2009 and 2010 to evaluate the efficacy of formulations of nicosulfuron (Nicomaïs 40SC), glyphosate (Roundup 360) and paraquat (Gramoxone 200g a.i./l) for weed control in maize. Treatments were nicosulfuron applied at 1 l/ha two weeks after planting maize, glyphosate applied at 6 l/ha before planting maize, paraquat applied at 6 l/ha with hoe weeded and unweeded control plots. Results showed that in both years, the weeded control and all herbicide treatments had lower weed density and dry matter, and higher grain yield than the unweeded control. The unweeded control had 1.3- 3.2 times more weeds than the herbicide treatments at crop harvest. Treatments with nicosulfuron gave the highest reduction in weed dry matter (92%). Treatments with glyphosate reduced weed dry matter by 59%, while those with paraquat gave a reduction of 49%. Maize grain yield in nicosulfuron treatments and the weeded control was similar and higher than that in treatments with glyphosate by 26%, those with paraquat by 51% and the unweeded control by 61%. The net gain of treatments with nicosulfuron was more than that with all other treatments. Nicosulfuron was more effective for weed control in maize than glyphosate and paraquat because it provided seasonal long control of the dominant weed species.